RECONFIGURABLE INTELLIGENT SURFACES (RIS) IN 6G NETWORKS: ENHANCING SPECTRAL AND ENERGY EFFICIENCY - Amjad Jumani,; Rozina Chohan,; Mirza Aqeel Ur Rehman,; Muhammad Taimoor Shahid,; Maria Soomro, (Spectrum of Engineering Sciences, 2025)
The outset of sixth-generation (6G) wireless networks is expected to respond to the escalating requests of ultra-reliable, high-capacity, energy-efficient systems brought by futuristic applications, including holographic telepresence, extended reality (XR), and intelligent automation. Reconfigurable Intelligent Surfaces (RIS), a new type of electromagnetic mirror made of meta-materials, have gained recognition as a disruptive technology that can dynamically engineer wireless propagation environments. This paper examines how RIS may be incorporated within 6G networks, as well as how it may affect spectral and energy efficiency in a variety of deployment settings. The research can substantiate that the RIS increases the efficiency of the spectrum usage by up to 43.7 percent, as well as displays energy efficiency by more than 60 percent relative to conventional 6G ones by modeling a downlink multi-user system with and without the assistance of RIS and artificial intelligence (AI)-based phase control. Extensive simulations in various configurations were performed to analyze eight detailed performance metrics including SINR, bit error rate, and coverage probability. The experimental outcomes affirms RIS as an inexpensive, passive, and smart means to resolve propagation constraints, decrease power, and improve the quality of connection in beyond-line-of-sight settings. The results provide useful information to network designers and policymakers contemplating sustainable and adaptive 6G infrastructures. Reconfigurable Intelligent Surfaces (RIS), 6G networks, spectral efficiency, energy efficiency, intelligent beamforming, AI control, next-generation wireless, wireless propagation, green communication, metasurfaces.